MEASURING SELF-ASSESSMENT OF STUDENTS’ CREATIVITY AT RIGA TECHNICAL UNIVERSITY - Maslak, Anatoly; van Gejeka, Nataļja; Pakrastiņš, Leonīds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the study is to measure the creativity of students at Riga Technical University on a linear scale of self-estimation. Self-estimation of students' creativity is assessed on the basis of indicators that are points of the corresponding questionnaire. The novelty of the study is that self-esteem of creativity is considered as a latent variable, which, in the framework of the theory of latent variables, is measured on a linear scale. In the framework of this theory, based on the Rasch model, an analysis of the quality of the questionnaire as a measuring tool is carried out. Three-way analysis of variance showed that the self-estimation of creativity of students of the Architectural faculty is statistically significantly higher than the self-esteem of creativity of students of the Construction faculty. The factors of students’ “gender” and “course” were noted as statistically insignificant. The results of the study should be used to analyse the quality of the educational process.